2016
DOI: 10.1021/acs.langmuir.6b01704
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Layer Engineering To Control Stability and Interfacial Properties of Nanoparticles

Abstract: The use of mixed ligand layers including poly(ethylene glycol)-based ligands for the functionalization of nanoparticles is a very popular strategy in the context of nanomedicine. However, it is challenging to control the composition of the ligand layer and maintain high colloidal and chemical stability of the conjugates. A high level of control and stability are crucial for reproducibility, upscaling, and safe application. In this study, gold nanoparticles with well-defined mixed ligand layers of α-methoxypoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 73 publications
6
48
0
Order By: Relevance
“…In the case of PEGylated materials, it has been shown that these conformations critically affect the immune response and the protein adsorption in general . The grafting density and structure of the polymer layer, or more generally ligand layer, also dictate the chemical and colloidal stability of NPs . Probing the structure of the ligand layer in solution is only possible with a few experimental methods.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of PEGylated materials, it has been shown that these conformations critically affect the immune response and the protein adsorption in general . The grafting density and structure of the polymer layer, or more generally ligand layer, also dictate the chemical and colloidal stability of NPs . Probing the structure of the ligand layer in solution is only possible with a few experimental methods.…”
Section: Resultsmentioning
confidence: 99%
“…For well‐defined samples, DLS can also be used to assess the thickness of the ligand layer but its resolution und accuracy are limited. For example, the increase of the hydrodynamic diameter from AuNP coated with citrate (shell thickness, s ≈ 1 nm) over AuNP coated with 2 kDa PEG (AuNP@PEG2k, s ≈ 6–10 nm) to AuNP@PEG5k ( s ≈ 10–14 nm) can be easily detected, but small changes of Δ s ≈ 1 nm of the hydrodynamic diameter cannot be detected with confidence. Additionally, even slight disturbances, for instance, caused by contaminations, aggregates, turbidity, microbubbles, viscosity, or adhesion to vessel walls can compromise the results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that the FluPep sequence did not reduce the stability of the gold nanoparticles under these standard conditions. A more stressful test is ligand exchange with small thiols (Chen et al, 2012, Duchesne et al, 2008a, Schulz et al, 2016, Schulz et al, 2013. Ligand-exchange results in a ligand shell that is unable to prevent electrolyte-induced aggregation of the nanoparticles, demonstrated by a decrease in the plasmon absorption at 520 nm.…”
Section: Stability Of Flupep Functionalised Gold Nanoparticlesmentioning
confidence: 99%
“…Furthermore, the spatial organization of the chains in mixed monolayers may strongly affect the particle's overall behavior . Several studies on AuNPs protected by patterned ligand arrangements of various types have addressed the role of the nanoscale arrangement of the ligands in mediating cellular interactions and the resulting physiological response .…”
Section: Introductionmentioning
confidence: 99%